Lightweight underwater robot developed for archaeological surveys and excavations - Shohei Hotta; Yusuke Mitsui; Mizuki Suka; Norimitsu Sakagami; Sadao Kawamura (ROBOMECH Journal, 2023)
Abstract This paper reports the development of a lightweight remotely operated vehicle that performs underwater excavation work for archaeological surveys. Discovering underwater artifacts is generally difficult because they are in high risk areas and are often covered with sediment. To discover them, divers and large remotely operated vehicles must conduct excavation work with a manipulator(s). Nevertheless, accomplishing such tasks is difficult for small and portable underwater robots without a manipulator(s). As described herein, we developed a lightweight underwater robot of 35 kg that can remove sediment from the seabed or lake bottom using its thrusters instead of a manipulator. Numerous redundant thrusters are equipped with the robot to compensate the reaction force of the thrusters for sediment removal. Eight thrusters are arranged not only for sediment removal but also for fine maneuvering. First, through preliminary experiments, we investigated the potential use of a water flow generated using a pair of small marine thrusters to remove surface sediment. Next, we described the design and development of a lightweight underwater robot with eight thrusters and high-definition cameras for archaeological surveys. Finally, we conducted field experiments to demonstrate the sediment removal performance and usefulness of the developed robot.